Triboelectric generator using mesoporous polydimethylsiloxane and gold layer - Mariatul Rawdhah Ahmad Fuaad; Lee Chang Yang; Farah Afiqa Mohd Ghazali; Mohamed Sultan Mohamed Ali (Bulletin of Electrical Engineering and Informatics, 2020)
This paper presents a triboelectric generator using mesoporous (PDMS) polydimethylsiloxane and gold layer which was demonstrated in energy harvesting applications. The performance of power generation by the means of triboelectric principle at a small dimension, namely triboelectric generator is characterized. In this paper, triboelectric generator device adapted vertical contact-separation operation mode, whereby the device derives power generation based on contact electrification caused by cyclic tapping motion. Being primarily a two-layer structure, this device comprises a top layer of aluminum (Al) electrode coated with mesoporous polydimethylsiloxane (PDMS) film and another bottom layer of Al electrode coated with gold (Au) deposit. The characterization of this device is done by varying frequencies and cyclic compression force applied to triboelectric generator. The optimal performance of the 2 cm x 2 cm triboelectric generator contact surface area generated an open-circuit voltage of 4.4 V and a current of 0.1 µA at 5 Hz frequency. This research and device can be improved by magnifying the effective surface area of triboelectric generator to generate significant power for small base area.